Antimicrobial action of silver nanoparticles (AgNps) stabilized in jurema preta (Mimosa tenuiflora (Willd., (Poir.) extract (Research, Society and Development, 2022)
Microbial drug resistance has been a threat to the effective treatment of various infections caused by pathogenic agents. In this sense, the research aimed to evaluate the antimicrobial action of silver nanoparticles (AgNPs) synthesized by means of bioreduction using the extract of Mimosa tenuiflora. With this, the research adopted the laboratory methodology of a quantitative nature in which it used for the synthesis of nanoparticles, silver nitrate (AgNO3) as a precursor agent, sodium citrate as a reducing agent and M. tenuiflora extract as a stabilizing agent. The inoculum of the bacterial species to be tested was prepared by the method of direct suspension of CLSI (2009) colonies in sterile saline solution, from colonies grown for 24 hours in BHI (Brain Heart Infusion agar) and in Sabouraud medium for the fungal species. The susceptibility test was performed using the CLSI (2009) well diffusion method, with adaptations, and the analysis of the antimicrobial action of AgNPs was performed after 24 hours of incubation at a temperature of 37 ºC. The solution containing AgNps was applied to three species of microorganisms: Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922) and Candida albicans (ATCC 10231). The results show that 20 µL of the substance against the microbial strains showed slight antimicrobial activity against bacteria, but the same was not observed in the tested yeast. According to the results, it is observed that the AgNps stabilized in M. tenuiflora have antimicrobial activity, mainly against Staphylococcus aureus.